Epigenetic Research in Stem Cell Bioengineering-Anti-Cancer Therapy, Regenerative and Reconstructive Medicine in Human Clinical Trials - Dompe, Claudia; Janowicz, Krzysztof; Hutchings, Greg; Moncrieff, Lisa; Jankowski, Maurycy; Nawrocki, Mariusz J; Józkowiak, Małgorzata; Mozdziak, Paul; Petitte, Jim; Shibli, Jamil A; Dyszkiewicz-Konwińska, Marta; Bruska, Małgorzata; et al. (Cancers, 2020)
The epigenome denotes all the information related to gene expression that is not contained in the DNA sequence but rather results from chemical changes to histones and DNA. Epigenetic modifications act in a cooperative way towards the regulation of gene expression, working at the transcriptional or post-transcriptional level, and play a key role in the determination of phenotypic variations in cells containing the same genotype. Epigenetic modifications are important considerations in relation to anti-cancer therapy and regenerative/reconstructive medicine. Moreover, a range of clinical trials have been performed, exploiting the potential of epigenetics in stem cell engineering towards application in disease treatments and diagnostics. Epigenetic studies will most likely be the basis of future cancer therapies, as epigenetic modifications play major roles in tumour formation, malignancy and metastasis. In fact, a large number of currently designed or tested clinical approaches, based on compounds regulating epigenetic pathways in various types of tumours, employ these mechanisms in stem cell bioengineering.
Keywords: cancer; reconstructive medicine; stem cells; regenerative medicine; epigenetics